Effect of grain sizes on mechanical properties and biodegradation behavior of pure iron for cardiovascular stent application. Issue 1 (1st January 2016) - Obayi, Camillus Sunday; Tolouei, Ranna; Mostavan, Afghany; Paternoster, Carlo; Turgeon, Stephane; Okorie, Boniface Adeleh; Obikwelu, Daniel Oray; Mantovani, Diego
ABSTRACT: Pure iron has been demonstrated as a potential candidate for biodegradable metal stents due to its appropriate biocompatibility, suitable mechanical properties and uniform biodegradation behavior. The competing parameters that control the safety and the performance of BMS include proper strength-ductility combination, biocompatibility along with matching rate of corrosion with healing rate of arteries. Being a micrometre-scale biomedical device, the mentioned variables have been found to be governed by the average grain size of the bulk material. Thermo-mechanical processing techniques of the cold rolling and annealing were used to grain-refine the pure iron. Pure Fe samples were unidirectionally cold rolled and then isochronally annealed at different temperatures with the intention of inducing different ranges of grain size. The effect of thermo-mechanical treatment on mechanical properties and corrosion rates of the samples were investigated, correspondingly. Mechanical properties of pure Fe samples improved significantly with decrease in grain size while the corrosion rate decreased marginally with decrease in the average grain sizes. These findings could lead to the optimization of the properties to attain an adequate biodegradation-strength-ductility balance.